Perbandingan Akurasi Metode TOPSIS dan Metode Weight Product untuk Menentukan Siswa Berprestasi - Abdul Fatahillah; Mudafiq Riyan Pratama (Puslitbang Sinergis Asa Professional, 2020)
In determining outstanding students (a case study at MTs. Al-Ishlah Jenggawah Jember) there are several criteria to be assessed. The criteria contained in student achievement in MTs. Al-Ishlah includes the average report card, behavior, discipline, neatness and attendance. For the sake of subjective assessment, an appropriate method is needed, namely the Technique for Others Reference by Similarity to Ideal Solution (TOPSIS) and Weight Product (WP). The purpose of this study is to compare the accuracy of TOPSIS and WP, ​​where each assessment in this case is that all students are compared with one another, thus providing an output of priority values ​​that produce a rating value for each student. After comparison and analysis, the accuracy of both methods was obtained, namely the TOPSIS method was 84% ​​while the WP method obtained an accuracy value of 87.5%. This means that in the case study, the determination of outstanding students is carried out at MTs. Al-Ishlah Jenggawah Jember showed that the WP method was better than the TOPSIS method.